Wavelet Characterization of Seismicity and Geomagnetic Coupling at Coastal Regions of Pakistan - Rashid, Syed M. Haroon; Yousufzai, M. Ayub Khan; Khan Afridi, Faisal Ahmed (Journal of Basic & Applied Sciences, 2017)
Earthquake recurrence is depicted on the basis of the time following subsequent seasons at the coastal regions of Pakistan. Recurrence time for intricate shock waves is simulated by using earth positions at equinoxes and perihelion-aphelion positions of the earth from the Sun. In connection to the spatial and temporal behavior of earth, the external geomagnetic variation is significant not only influenced by the distances between the Sun and earth and annual revolving period of earth around the Sun at heliocentric path but also affected by a lunar revolving period on an elliptical path around the earth. The Apparent path of the Sun during the year where earth is the center of the celestial sphere and relative to earth, the Sun appears on ecliptic sphere which intersects the celestial equator in two points known as the vernal equinox of 21st march and autumn equinox of 21st September. The perihelion position on earth is nearest to the Sun and aphelion is the furthest position of the earth from the Sun, these are empirically distributed on the basis of mutual interaction. The seasonal effects are recognized by the wavelet characterization on maximum amplitudes of shock waves with reference to vernal – autumn equinoxes of distributed perihelion-aphelion periods. The seasonal period of geomagnetic seismicity is a manifestation of the mean time between earthquakes within a specified region where many faults are activated. The cyclic nature of earthquakes and geomagnetic influences on seismic waves by stress-strain tectonic process and releasing energy for the relaxation mechanism are experienced in nature, therefore the issues relevant to their aphelion – perihelion periodicities, influential conditions of geomagnetic instability and their coupling for shock waves propagation are tackled by the wavelet applications.